# Yahoo奇摩 網頁搜尋

1. ### algebraic expression

Okay. But I am not sure what&#39;s your level of education.. But I will still suggest three questions for you. High School Level: 1. Show that e ^iθ + e ^ -iθ = 2cosθ. Hence, or otherwise, show that cos...

分類：科學及數學 > 數學 2006年11月18日

2. ### algebraic expression (1)

1. (n*n*...*n)/(n+n+...+n) = [n/(n+n...+n)]^n = (1/n)^n = 1/(n^n) 2. (x^2 - √(3x) + 1)(x^2 + √(3x) + 1) = x^4 + x^2 √(3x) + x^2 - x^2 √(3x) - √(3x) + x^2 + √(3x) + 1 = x^4 + 2x^2 + 1 = (x^2 + 1)^2 3. a^2 - 2ab + b^2 - a + b = (a-b)^2 - (a-b) = (a-b)(a-b-1) 4. 3x^2 + 6x + 1 = 3(x+b)^2 + c => 3x^2 + 6x + 1 = 3x^2 + 6bx + (3b^2 + c) Comparing...

分類：科學及數學 > 數學 2012年01月29日

3. ### F1.MATHS Algebraic Expression

Carmen weights y kg,Fanny is 10kg heavier than Carmen Therefore Fanny weights y+10 kg y+y+10=73 y=31.5 Fanny weights y+10 kg So Fanny weights 41.5 kg

分類：科學及數學 > 數學 2011年10月19日

4. ### Simplify set expressions

http://i1090.photobucket.com/albums/i376/Nelson_Yu/int-50.jpg 圖片參考：http://i1090.photobucket.com/albums/i376/Nelson_Yu/int-50.jpg

分類：科學及數學 > 數學 2011年09月24日

5. ### Simplify the following expressions

1. (-4a-12b+8c)÷(-4) = -4a/-4 - 12b/-4 + 8c/-4 = a + 3b - 2c 2. (15m^3 - 5m^2 - 10m) ÷ (-5m) = 15m^3/-5m - 5m^2/-5m - 10m/-5m = -3m^2 + m + 2 3. 12y^3 -12y^2 +6y 　－－－－－－－－ 　　　-3y = 12y^3/-3y - 12y^2/-3y +6y/-3y =-4y^2 + 4y - 2 4. 16a^3b-36ab^3 　－－－－－－－ 　　　 4ab = 16a^3b/4ab - 36ab^3/4ab = 4a^2 - 9b^2

分類：科學及數學 > 數學 2007年08月16日

6. ### Simplify the following... expressions

1) x^4-y^4/c+d X c^2-d^2/x+y X x^2/x-y =(x^2-y^2)(x^2+y^2)/(c+d)X(c-d)(c+d)/(x+y)Xx^2/x-y =(x+y)(x-y)(x^2+y^2)/(c+d)X(c-d)(c+d)/(x+y)Xx^2/x-y =(x^2+y^2)x(c-d)x(x^2) 2) x^4+x^2y^2+y^4/x^2-2xy-15y^2 X x^2+2xy-3y^2/x^3-y^3 X x-5y/1 =x^4+2x^2y^2-x^2y^2+y^4/(x+3y)(x-5y)X(x-3y)(x+y)/(x-y...

分類：科學及數學 > 數學 2008年07月10日

7. ### algebraic expression &phrases !

I use n dollars to buy an apple,I changed(找錢) 1 dollars. Using algebraic to express the price of an apple: The price of an apple: n-1

分類：科學及數學 > 數學 2010年07月28日

8. ### expression for the total surface area of a cylinder

Total surface for a solid cylinder = 2(pi)r^2 + 2(pi)rh , h = height of cylinder If you are considering a cylinder with one side opened, you should use (pi)r^2 instead of 2(pi)r^2

分類：科學及數學 > 數學 2007年10月25日

9. ### Rewriting an expression

consider a right angled-triangle with angle θ s.t. sinθ=x/4 i.e. opposite side=x , hypotenuse=4 ∴adjacent side=√(4^2-x^2)=√(16-x^2) (Pyth. theorem) 8 cos(arcsin x/4) =8cosθ =8(√(16-x^2) / 4) =2√(16-x^2)

分類：科學及數學 > 數學 2014年04月14日

10. ### How to simplify this expression ?

Sol A=√(x－1)，B=√x，C=√(x+1) AB=√(x^2－x) BC=√(x^2+x) C^2－B^2=1 A^2－B^2=－1 √(x－1)/(√(x+1)－√x))+(√(x+1)/(√(x－1)+√x)) =A/(C－B)+C/(A+B) =(AC+AB)/(C^2...

分類：科學及數學 > 數學 2017年09月13日